Solar power optimiser for smart hybrid DC-AC grid - Lin, Binghong. (2013)
Renewable energy has been increasingly popular since it is pollution free and the source of energy is unlimited. Photovoltaic is one of the most common technology but the conversion rate of solar into electrical energy is heavily dependent on environmental factors. This project explores a design method of photovoltaic system which incorporates 3 photovoltaic panels and 3 DC-DC boost converters. The converters step up DC voltage provided by the solar panels individually, producing a total output voltage of 230V. Whenever one of the panels is covered by clouds, it would prompt the other 2 converters to boost additional voltage in order to maintain the desired output signal. Furthermore, the boost converter will return to their default operation when the sky is cleared.